The Natural Radioactivity in Food: A Comparison Between Different Feeding Regimes - Caridi, Francesco; Marguccio, Santina; Belvedere, Alberto; D`Agostino, Maurizio; Belmusto, Giovanna (Current Nutrition & Food Science, 2019)
Background: In this article a comprehensive study was carried out for the determination of natural radioactivity in animal and vegetable food (meat, fish, milk and derivates, legumes, cereals and derivates, fruit, hortalizas, vegetables, vegetable oils) typical of different feeding regimes, for the age category higher than 17 years. Methods: A total of eighty-five samples of Italian origin, coming from large retailers during the years 2014, 2015 and 2016, were analyzed through HPGe gamma spectrometry. Results: The specific activity of 40K was investigated and its mean value was found to be: (106.3 ± 6.9) Bq/kg for bovine, swine and sheep meat; (116.5 ± 9.7) Bq/kg for fish; (52.9 ± 3.1) Bq/kg for milk and derivates; (271.9 ± 16.7) Bq/kg for legumes; (67.2 ± 4.7) Bq/kg for cereals and derivates; (52.7 ± 4.4) Bq/kg for fruit; (72.9 ± 5.6) Bq/kg for hortalizas; (83.9 ± 6.5) Bq/kg for vegetables; lower than the minimum detectable activity for vegetable oils. For animal food the highest mean 40K activity concentration was found in fish samples; for vegetable food the highest one was detected in legumes. Conclusion: The evaluation of dose levels due to the food ingestion typical of Mediterranean, Vegetarian and Vegan diets was performed. The annual effective dose was found to be 0.16 mSv/y, 0.41 mSv/y and 0.54 mSv/y, respectively.
Keywords: food